SIMPLE FORMS OF ZIRCON CRYSTALS FROM CRYSTALLINE ROCKS OF THE UKRAINIAN SHIELD AND THEIR MORPHOLOGICAL TYPES - Kvasnytsya, I.; Kvasnytsya, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The main basics in geometric crystallography of zircon, developed by many researchers in the 18th - 20th centuries, are briefly described. The data of goniometric study of zircon from crystalline rocks of the Ukrainian Shield (USh) are summarized. They cover zircon predominantly from granites and alkaline rocks of most the USh megablocks. The set of habit simple forms on zircon crystals is small: {111}, {110}, {100}, {221}, {331} and {311}. These forms define two contrasting habits of zircon crystals - prismatic and dipyramidal. Among the prismatic crystals several main morphological types of crystals are distinguished: {110} + {111} – zircon type, {100} + {111} – hyacinth type, {110} +100} + {111}, {110} +{100} + {111} + {311} and {110} + {100} + {311} – intermediate hyacinth-zircon types. Among the dipyramidal crystals two morphological types are contrasting — faceted by {111} dipyramid and {111} + {331} + {221} dipyramid combinations. The simple form {111} is developed on almost all zircon crystals from crystalline rocks of the USh, unless it is completely displaced on the heads of the crystals by the ditetragonal dipyramid {311}. For zircon crystals from syenites, mariupolites, albitites and some pegmatites the {111} is habit form. The simple form prism {110} is also developed on almost all zircon crystals from crystalline rocks of the USh, with the exception of many {111} dipyramidal crystals from syenites of the Zhovtnevy massif and hyacinth type of zircon crystals. It determines the most common morphological type of zircon crystals of prismatic habit – zircon type. The simple form prism {100} is less common on zircon crystals from crystalline rocks of the USh than the form {110}. It determines the hyacinth morphological type of zircon crystals of a prismatic habit. It is characteristic of zircon from granites of the Azov and Middle Dnipro regions. The simple form {311} is well developed on zircon crystals of hyacinth-zircon type from granites. It is almost absent on dipyramidal zircon crystals from alkaline rocks. The simple forms {221} and {331} are well developed only on dipyramidal crystals from syenites, mariupolites, albitites and some pegmatites of the Azov region. They are especially characteristic of zircon crystals of the Azov deposit. The simple form pinacoid {001} is rare and poorly developed; it was found only on zircon crystals of a prismatic habit from carbonatites of the Chernigiv massif and on dipyramidal crystals from syenites of the same massif. Another two dipyramids {101} and {211} can be attributed to reliable simple forms on zircon crystals from crystalline rocks of the USh. However, they are rare and found only on zircon crystals from acid rocks. Other goniometrically studied simple forms are poorly developed and incomplete, their reliability is questionable and therefore not accepted by us for consideration. The data presented on simple forms, habits and the main morphological types of zircon crystals from crystalline rocks of the USh almost completely confirm the main points on the morphological and structural bases of the crystallomorphology of zircon. First of all, this concerns two contrasting habit types of zircon crystals: dipyramidal crystals grow mainly in alkaline rocks and various morphological types of prismatic crystals grow in acidic rocks. In general, the set, the degree of importance and the distribution of simple forms on zircon crystals from crystalline rocks of the USh correspond to the morphological and structural series of crystals of this mineral. At the same time, the diversity of the morphological types of prismatic zircon crystals from granites still does not have a proper explanation. For the time being, it can be stated that each petrological type of granite can be characterized by a specific morphological type or types of prismatic zircon crystals. The dipyramidal zircon from most manifestations of alkaline rocks of the USh is younger than prismatic zircon from acidic rocks of the USh. Zircons from syenites of the Yastrubetsky and Zhovtnevy massifs and the Azov deposit have a Paleoproterozoic age of ∼1770 Ma. It characterizes the only stage of Paleoproterozoic alkaline magmatism, powerfully manifested in the USh and rich in rare-earth geochemical specialization. Dipyramidal zircons in these rocks are prevalent and even dominate (in mariupolites of the Zhovtnevy massif and syenites of the Azov deposit). Zircons from syenites and carbonatites of the Chernigiv massif, among which there are more rare dipyramidal crystals, are much more ancient - about 2000 Ma. Zircons from acidic rocks of the USh formed mainly in the period of 2.2–1.8 billion years. The dipyramidal zircon on the USh is a Precambrian formation, which reflects the Paleoproterozoic stage of the USh history, which is relatively narrow in time. Such zircon occurs in the Neogene and Quaternary terrigenous sediments of the southwestern part of the USh, which may indicate the presence in this area of still unknown Paleoproterozoic sources of alkaline magmatism. Dipyramidal zircon crystals may also belong to different albitized rocks and pegmatites of acidic and alkaline rocks.
Keywords: zircon; crystallomorphology; simple forms; morphological types; the Ukrainian Shield